Legal Protection for Other Creators Whose Works are Used in Artificial Intelligence Data Systems in Terms of the Law on Copyright - Rahmasari, Nindy Alievia; Purwanto, Aldira Mara Ditta Caesar (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
This study investigates the complex legal landscape surrounding artificial intelligence (AI) and its impact on copyright law. By examining cases that have occurred in the world, the study explains the challenges in protecting AI-generated works as well as the legal protections through Law No. 28 of 2014 on Copyright that have until now accommodated the concept of legal protection of the exclusive rights of creators. This research underscores the need for a strong legal framework to uphold the rights of creators and effectively regulate the intersection of AI and copyright that continues to grow rapidly in today's technological era. This research uses a normative juridical approach with the aim of determining the meaning of a concept and legal rules that will be used as a reference in the process of solving legal problems that have become the focus of research. Data for this research was collected from various sources including books, scientific journals, and legislation. The findings in this study show the results that there are regulations that are considered similar in concept in terms of legal protection for creators formed in two aspects, namely preventive and repressive. However, this cannot exclude the fact that regulations related to artificial intelligence and the legality of its practice in Indonesia remain an urgency for the government to formulate in order to respond and solve similar problems by reflecting on the practice of cases that have occurred in several countries as mentioned earlier.